2019
DOI: 10.18203/2394-6040.ijcmph20191380
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cancer: perception of peripheral health workers in Lucknow: a cross-sectional study

Abstract: Background: Cervical cancer is one of the most prevalent cancers among Indian women. Cervical cancer incidence reduces dramatically when effective screening programs linked with access to treatment are in place and are readily accessible. Peripheral health workers (PHWs) being frontline workers have a major influence on raising awareness among community about acceptability of available screening programmes. This study was thus conducted to assess the awareness of PHWs regarding risk factors, signs and symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Findings similar to ours were observed in a study conducted in Lucknow, where about two-third of the ASHAs scored below average. 23 We found that about one-fourth of the ASHAs and half of the ANMs knew about Clinical Breast Examination as a screening method; however, less than one-fourth of the ANM could correctly demonstrate all the steps of breast examination. Similar findings were observed in a study conducted in Himachal Pradesh, where the majority of the health workers could not able to perform breast examination.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Findings similar to ours were observed in a study conducted in Lucknow, where about two-third of the ASHAs scored below average. 23 We found that about one-fourth of the ASHAs and half of the ANMs knew about Clinical Breast Examination as a screening method; however, less than one-fourth of the ANM could correctly demonstrate all the steps of breast examination. Similar findings were observed in a study conducted in Himachal Pradesh, where the majority of the health workers could not able to perform breast examination.…”
Section: Discussionmentioning
confidence: 76%
“…25 In the present study, knowledge score for NCDs was found to be higher among those who had received previous training for NCDs; similar results were found in various studies conducted in India and abroad. 20,22,23 Skills for measuring blood pressure, blood sugar and breast examination were found to be low among the ANMs. Similar findings were observed in a study conducted in Himachal Pradesh, where a contracted proportion i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Assuming level of awareness for female cancers in peripheral health workers as 65%, taking design effect of 2, sample size of 450 was calculated. In rural areas, 325 PHWs (232 ASHAs and 93 BHWs) and 125 PHWs (90 BHWs and 35 ASHAs) from Urban CHCs were selected and interviewed [5].…”
Section: Sample Size and Sampling Methodsmentioning
confidence: 99%
“…3 There is an urgent need of organizing awareness and screening programs for cervical cancer in the rural women masses which can be achieved through trained health workers and by organizing camps for the early detection of the disease through proper counseling and motivation of women in the villages. 4 With an aim to provide the facility to detect early cases of cervical cancer to rural women, a cervical cancer screening program was initiated under the auspices of Era's Lucknow Medical College and Hospital, Era University, Lucknow in May 2013 in the villages of three blocks of western Lucknow by organizing camps. Till February 2020, a total of 186 camps were organized and 5286 women attended these camps.…”
Section: Introductionmentioning
confidence: 99%